EFEKTIVITAS MEDIA ALAM SEBAGAI SARANA MENINGKATKAN MINAT BELAJAR ANAK, DI SD NEGERI 33, KAMPUNG SWATUT MALAUMKARTA, DISTRIK MAKBON, KABUPATEN SORONG, PAPUA BARAT - NATASYA VIRGINIA LEUWOL; WINDY WONMALY; MARISSA A TUMAMAHU (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This study aims to determine the effectiveness of natural media as a means to increase children's interest in learning at SD Negeri 33, Swatutu Malaumkarta Village, Makbon District, Sorong Regency, West Papua. The method used is qualitative research to answer research problems related to student interest in learning obtained from the learning process, interview, observation and documentation. Qualitative research aims to design students for a general understanding of social reality from the participant's perspective, then the results of the research are analyzed using several data analysis techniques, namely extending observations, increasing persistence, and field analysis. The results of the research obtained are natural media as an effective means to increase children's interest in learning at SD Negeri 33, Sorong Regency. Natural media really gives freedom to students in expressing their thoughts to obtain contextual learning and can be used as a reference in learning at school. Children in the teaching and learning process become free to develop what they know, see, and feel. Learning by using natural media, can be evaluated to maximize teaching and learning processes and outcomes. The supporting factors for using natural media in this study are the availability of wide and beautiful nature, as well as the comprehensive use of the natural environment. The limiting factors are time and weather. However, this is not an obstacle for teachers to apply natural media in the learning process to increase children's interest in learning.